KINERJA KEUANGAN, INFLASI, DAN RETURN SAHAM : STUDI PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - ALDIA HIDAYANI, YUNIA; HARTONO, ULIL (Jurnal Ilmu Manajemen (JIM), 2019)
The number of investors in Indonesia has increased from 2012 to 2018. Because investment people aim to get a profit or return. Stock returns are calculated based on fluctuations in stock prices. Many factors can influence the size of stock returns. So the purpose of this study is to determine the effect of financial performance ( ROA, ROE, DER, PER, EPS, EVA, Cash Flow ) and inflation on stock returns in mining sector companies listed on the Indonesia Stock Exchange for the period 2015-2017. The analysis technique used in this study is multiple linear regression analysis with a total sample of 34 companies. The results of this study show together the variables ROA, ROE, DER, PER, EPS, EVA, Cash Flow and inflation affect stock returns. Partially or individually, the PER variable affects stock returns. The increasing PER value will increase stock returns, and show good corporate growth in the future. EPS affects stock returns, where the high EPS value shows a high return value. The variables ROA, ROE, DER, EVA, cash flow, and inflation have no effect on stock returns. Investors do not make these variables a consideration in investing to look for a profit or return. Keywords: financial performance; inflation; stock returns.